Pitfalls of Public Choice: Polemic with Marek Loužek's "Can Public Choice Theory Explain EU Enlargement?" (Czech Journal of International Relations, 2005)
Úskalí veřejné volby. Polemika ke stati Marka Loužka: Dokáže teorie veřejné volby vysvětlit rozšiřování Evropské unie?